A Rare Case of Takotsubo Syndrome and Acute Coronary Syndrome of the Right Coronary Artery - Nicholas Mencer; Larry Todd Justice; William Black; Kayleigh Litton (Case Reports in Cardiology)
Takotsubo syndrome (TTS) is an increasingly recognized heart disease that was initially regarded as a benign condition, but since has proven to cause irreversible myocardial damage, resembling that of acute coronary syndrome (ACS). The etiology of TTS is still uncertain but may be associated with catecholamine elevations during times of emotional or physical stress. Catecholamines are also understood to have prothrombotic properties, which could lead to ACS. With these similarities, differentiating these two pathologies can be difficult, especially when TTS and ACS occur simultaneously.